Optimization of Management Functions in Administrative Services at SMK Kartika XX-1 Makassar - Saputri, Ananda; Akib, Haedar; Saleh, Sirajuddin (Journal of Public Policy and Local Government (JPPLG), 2024)
The administrative management function refers to the set of activities and responsibilities required to ensure that school administration runs smoothly and efficiently. The main purpose of this study is to find out the application of management functions to administrative services at SMK Kartika XX-1 Makassar and to find out the supporting and inhibiting factors in optimizing administrative services at SMK Kartika XX-1 Makassar. This study uses a qualitative approach with a type of descriptive research that focuses on the application of management functions based on indicators of planning, organizing, directing, and supervising. The data collection techniques used are observation, interviews, and documentation. Based on the results of the study, it shows that the optimization of the management function in administrative services at SMK Kartika XX-1 Makassar can be said to be "Quite Optimal", This is shown through management indicators, namely: 1) Administrative planning is carried out systematically through deliberations led by the principal, head of administration, and involving all staff, to discuss and prepare annual program planning by paying attention to the needs of staff,  education customers, and the need for service support facilities; 2) The organization of administration starts from the determination of administrative tasks, followed by the recruitment and selection of administrative personnel, as well as the division of tasks according to the field and competence of each staff; 3) Administrative briefings are carried out directly by the principal, either personally or through meetings. Briefing and motivating activities aim to ensure that all staff understand their duties and responsibilities, the school's goals, and the efforts taken in achieving these goals; and 4) Administrative supervision is carried out every day, where the principal goes directly to supervise the performance of staff, identify staff needs, and provide appropriate solutions to obstacles that staff may face in carrying out their duties and responsibilities